2007
DOI: 10.1063/1.2409929
|View full text |Cite
|
Sign up to set email alerts
|

Relaxations and nano-phase-separation in ultraviscous heptanol-alkyl halide mixture

Abstract: To gain insight into the effects of liquid-liquid phase separation on molecular relaxation behavior we have studied an apparently homogeneous mixture of 5-methyl-2-hexanol and isoamylbromide by dielectric spectroscopy over a broad temperature range. It shows two relaxation regions, widely separated in frequency and temperature, with the low-frequency relaxation due to the alcohol and the high-frequency relaxation due to the halide. In the mixture, the equilibrium dielectric permittivity s of the alcohol is 41%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 50 publications
3
41
1
Order By: Relevance
“…1 for the temperature range 109.2-140.3 K in which the dispersion and absorption features due to each component are clearly distinct. As seen in our study of 5-methyl-2-hexanol-iso-amylbromide mixture, 26 and as was observed previously by Denney 17 for the 1-propanol-isoamylbromide mixture, the spectra show two dispersion regions in Ј and two peaks corresponding to these dispersions in Љ. The lower frequency dispersion and the Љ peak correspond to Brownian diffusion of 1-propanol while the higher frequency peak is associated with the isoamylbromide molecules.…”
Section: Resultssupporting
confidence: 64%
See 4 more Smart Citations
“…1 for the temperature range 109.2-140.3 K in which the dispersion and absorption features due to each component are clearly distinct. As seen in our study of 5-methyl-2-hexanol-iso-amylbromide mixture, 26 and as was observed previously by Denney 17 for the 1-propanol-isoamylbromide mixture, the spectra show two dispersion regions in Ј and two peaks corresponding to these dispersions in Љ. The lower frequency dispersion and the Љ peak correspond to Brownian diffusion of 1-propanol while the higher frequency peak is associated with the isoamylbromide molecules.…”
Section: Resultssupporting
confidence: 64%
“…26 This is the opposite of the change in observed for 1-propanol-isoamylbromide mixture. 17,24 In view of the interpretation of the Debye-type spectra in terms of the relaxation by hydrogen bond breaking and reforming, [1][2][3][11][12][13][14]27,28 and our findings for the 5-methyl-2-hexanol mixture, 26 we have restudied the dielectric behavior of 1-propanol-isoamylbromide mixture in detail and have examined its crystallization behavior in real time by using broad band spectroscopy. Studies on their pure liquid states have been reported in earlier papers, 16,22 and are used for comparison.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations